EXAMINING HOUSING EXPERIENCES OF URBAN REFUGEES IN KLANG VALLEY, MALAYSIA - Alam, Fariba; Tedong, Peter Aning; Zyed, Zafirah Al Sadat (Journal of Surveying, Construction and Property, 2025)
Malaysia has hosted refugees without a formal refugee policy or legal framework for many decades. The absence of adequate accommodation and reception facilities for refugees and asylum seekers, coupled with insufficient housing during their transitional period before resettlement, presents significant challenges. These "living in limbo" conditions exacerbate uncertainty, violence, and insecurity in refugees’ lives. This paper aims to examine housing experiences of urban refugees in the Klang Valley. The research involved a survey of 196 refugees, predominantly from Sudan, Somalia, Yemen, Afghanistan, and Myanmar residing in Klang Valley. The findings provide critical insights into the housing experiences of refugees in Malaysia. The findings found that Refugees are satisfied with the building services, unit design, provision of kitchen and laundry spaces, and basic facilitates. Satisfaction level is also quite significant in terms of building cleanliness and maintenance. However, they indicated significant discrimination in securing rental accommodations, as landlords are reluctant to lease properties to refugees. Additionally, many refugees encounter difficulties due to frequent rent hikes. The insights gained from this study can assist stakeholders in addressing these challenges and enhancing the management and support provided to the refugee community, paving the way for further exploration and implementation of effective solutions.